2003
DOI: 10.1002/path.1292
|View full text |Cite
|
Sign up to set email alerts
|

hnRNP B1 expression in benign and malignant lung disease

Abstract: Evidence is accumulating to suggest that hnRNP B1 expression may be a useful tool in the early diagnosis of lung cancer. This study examined the immunohistochemical expression of hnRNP B1 in archived sections of resected lung cancers and compared the patterns of expression with those seen in similar archived sections of non-neoplastic lung. Particular attention was paid to the expression of hnRNP B1 in the benign bronchial cells in both cases, to establish if overexpression of this protein in respiratory epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In other reports, some positive staining of normal cells (albeit of lower intensity than with cancer cells) has been detected with two monoclonal anti-B1 antibodies [23,28,35]. In an exclusive immunohistochemical study using archived tissue sections of resected lung cancers in parallel with control non-cancer tissues from benign lung disease unrelated to cancer, B1 expression was also seen (at a frequency of 25%) in benign bronchial epithelial cells and inflammatory cells of the control group [28]. Nonetheless, hnRNP B1 expression is seen from the early stages of malignant transformation (in occult cancer, bronchial dysplasia and sputum) and is currently considered to be a more specific and sensitive biomarker than hnRNP A2/B1 for the early detection of lung cancer [24,25,27].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In other reports, some positive staining of normal cells (albeit of lower intensity than with cancer cells) has been detected with two monoclonal anti-B1 antibodies [23,28,35]. In an exclusive immunohistochemical study using archived tissue sections of resected lung cancers in parallel with control non-cancer tissues from benign lung disease unrelated to cancer, B1 expression was also seen (at a frequency of 25%) in benign bronchial epithelial cells and inflammatory cells of the control group [28]. Nonetheless, hnRNP B1 expression is seen from the early stages of malignant transformation (in occult cancer, bronchial dysplasia and sputum) and is currently considered to be a more specific and sensitive biomarker than hnRNP A2/B1 for the early detection of lung cancer [24,25,27].…”
Section: Discussionmentioning
confidence: 96%
“…The application of polyclonal antibodies exclusively recognising the hnRNP B1 variant resulted in strong nuclear staining, mainly of squamous cell carcinoma, but not of the normal lung epithelial cells adjacent to tumours [24,27]. In other reports, some positive staining of normal cells (albeit of lower intensity than with cancer cells) has been detected with two monoclonal anti-B1 antibodies [23,28,35]. In an exclusive immunohistochemical study using archived tissue sections of resected lung cancers in parallel with control non-cancer tissues from benign lung disease unrelated to cancer, B1 expression was also seen (at a frequency of 25%) in benign bronchial epithelial cells and inflammatory cells of the control group [28].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Haptoglobin [181], fragment of apolipoprotein A-1 [142] and heterogeneous ribonuclear proteins A2/B1 (hnRNP A2/B1) [182] are also mentioned as lung cancer biomarkers with controversial results.…”
Section: Unlimited Growth Potential Pathwaymentioning
confidence: 99%
“…More recently, cyclin D1 overexpression has also been reported to participate in activation of ALT in combination with p53 inactivation in a cancer model using human oral keratinocytes (12). Heterogeneous nuclear ribonucleoproteins (hnRNPs) A2/B1 have reported to be overexpressed in various cancers (13)(14)(15)(16)(17), and also have attracted considerable attention as proteins that bind to single-stranded telomeric DNA (18,19). We previously reported that B1 has stronger affinity for telomeric DNA than A2 and may be an important factor for telomere maintenance (20).…”
Section: Introductionmentioning
confidence: 99%